Properties of graphene deposited on GaN nanowires: influence of nanowire roughness, self-induced nanogating and defects - Kierdaszuk, Jakub; Kaźmierczak, Piotr; Grzonka, Justyna; Krajewska, Aleksandra; Przewłoka, Aleksandra; Kaszub, Wawrzyniec; Zytkiewicz, Zbigniew R.; Sobanska, Marta; Kamińska, Maria; Wysmołek, Andrzej; Drabińska, Aneta (Beilstein Journal of Nanotechnology, 2021)
We present detailed Raman studies of graphene deposited on gallium nitride nanowires with different variations in height. Our results indicate that different density and height of nanowires impact graphene properties such as roughness, strain, and carrier concentration as well as density and type of induced defects. Tracing the manifestation of those interactions is important for the application of novel heterostructures. A detailed analysis of Raman spectra of graphene deposited on different nanowire substrates shows that bigger differences in nanowires height increase graphene strain, while a higher number of nanowires in contact with graphene locally reduces the strain. Moreover, the value of graphene carrier concentration is found to be correlated with the density of nanowires in contact with graphene. The lowest concentration of defects is observed for graphene deposited on nanowires with the lowest density. The contact between graphene and densely arranged nanowires leads to a large density of vacancies. On the other hand, grain boundaries are the main type of defects in graphene on rarely distributed nanowires. Our results also show modification of graphene carrier concentration and strain by different types of defects present in graphene. Therefore, the nanowire substrate is promising not only for strain and carrier concentration engineering but also for defect engineering.
Keywords: carrier concentration; gallium nitride; graphene; nanowires; Raman spectroscopy; scattering on defects; strain